Influence of chemical reaction on the heat and mass transfer of nanofluid flow over a nonlinear stretching sheet: A numerical study - Misra, Santoshi; Govardhan, K. (Zielona Góra: Uniwersytet Zielonogórski)
A numerical study on a steady, laminar, boundary layer flow of a nanofluid with the influence of chemical reaction resulting in the heat and mass transfer variation is made. The non-linear governing equations with related boundary conditions are solved using Adam`s predictor corrector method with the effect of a Brownian motion and thermophoresis being incorporated as a model for the nanofluid, using similarity transformations.
Keywords: nanofluid; Brownian motion; thermophoresis; chemical reaction; heat transfer; mass transfer